Built form properties as sign and symbols of patron political ideology - Alice Sabrina Ismail,; Erna Nuralia Zhaharin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper discusses on the study of architecture as a sign system by analyzing its generic elements-form making based on the Western philosophers. In addition, this study investigates how built form act as a sign and contribute to major symbolic content which gives concrete expression to the socio cultural and political phenomenon. In this case, prominent buildings found in the modern context are used as examples to explain how they are capable of communicating the intentions of patrons to users as well as transmitting messages when users invest the building with meaning. This is important as built form do not only symbolize norms of society and social structure as well that relative to world view, hierarchies and the like. This paper is significant as it develops a systematic approach to understand the relationship between sign symbols and material culture. This understanding makes substantive contribution to elucidate the production of meaning in relation to the built environment across different cultural settings. Furthermore, it provides an insight that the meaning of the built environment is dependent on human intentions and purposes as conceived in a particular cultural context like Malaysia and the global scene. Therefore, it provides a clear framework to lead architectural scholars, designers and researchers, who are interested in analysing the themed environments, towards a better understanding of the structural relationship that exists between the built environment and social culture in contemporary society.